1998
DOI: 10.3109/13625189809051409
|View full text |Cite
|
Sign up to set email alerts
|

A 4-year pilot study on the efficacy and safety of Implanon®, a single-rod hormonal contraceptive implant in healthy women in Thailand

Abstract: Implanon demonstrated excellent contraceptive efficacy and was well tolerated during up to 4 years of use. The vaginal bleeding pattern was variable and was characterized by relatively few bleeding events, but proved acceptable to most subjects. Because of its single-rod design, Implanon was quickly inserted and removed without complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 12 publications
2
23
0
Order By: Relevance
“…A significantly increased frequency of nausea and dizziness was noted in this, as in other studies 10 . Some investigators reported headache to be the most common non-menstrual side effect 10,11 . The increased frequency of headache among the subjects we investigated was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…A significantly increased frequency of nausea and dizziness was noted in this, as in other studies 10 . Some investigators reported headache to be the most common non-menstrual side effect 10,11 . The increased frequency of headache among the subjects we investigated was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Bhatia et al reported common adverse events of amenorrhoea, irregular menses, weight gain, acne, and headache. 2 Headaches were non-specific and occurred in 7% of users, whereas weight gain of 45 kg was reported in 7.5% over a 3-year period.…”
Section: Introductionmentioning
confidence: 99%
“…In longterm users of the LNG-IUD, a small increase in weight has been demonstrated, but this is equivalent to the weight gain associated with increasing age and no different from the weight gain observed in randomized studies compared to copper IUD users [32,33]. A paucity of studies exists with regard to the etonorgestrel implant (Implanon) but the available evidence suggests a minimal to zero impact on weight [34,35]. Again, these studies have been performed in non-obese women so it is yet unknown if a weight change would occur in an obese woman.…”
Section: Body Weightmentioning
confidence: 91%